2021
DOI: 10.1016/j.xcrm.2021.100242
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mapping of SARS-CoV-2 and H1N1 lung injury identifies differential transcriptional signatures

Abstract: Highlights d SARS-CoV-2 and H1N1-induced ARDS show unique transcriptional signatures d Tissue remodeling pathways dominate the transcriptional profile of SARS-CoV-2 ARDS d SARS-CoV-2/H1N1 double infection resembles the lung antiviral response to H1N1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…The unique phenotype of COVID-related lung injury was confirmed by Margaroli et al [28], who, by means of a spatial transcriptomic platform on autopsy-derived lung tissue, documented a more firboproliferative response of SARS-COV-2 infection versus H1N1. Overall, due to the distint fibrotic and prothrombotic ARDS phenotype of COVID-19, pulmonary vasculature is largely affected, being responsible for the increased RV afterload, and therefore possibly contributing to RV alterations especially in severe COVID-related ARDS.…”
Section: Resultsmentioning
confidence: 74%
“…The unique phenotype of COVID-related lung injury was confirmed by Margaroli et al [28], who, by means of a spatial transcriptomic platform on autopsy-derived lung tissue, documented a more firboproliferative response of SARS-COV-2 infection versus H1N1. Overall, due to the distint fibrotic and prothrombotic ARDS phenotype of COVID-19, pulmonary vasculature is largely affected, being responsible for the increased RV afterload, and therefore possibly contributing to RV alterations especially in severe COVID-related ARDS.…”
Section: Resultsmentioning
confidence: 74%
“…Note: red font: upregulation, blue font: downregulation in this study. Studies compared include Margaroli et al 2021 [ 41 ], Grant et al 2021 [ 42 ], Desai et al 2020 [ 43 ] and Butler et al 2021 [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported massive immune cell infiltration in the lungs during severe COVID-19, indicative of severe COVID-19 as a manifestation of a hyperinflammatory state in which the maladaptive immune response itself can cause lung issue injury. Diffuse inflammatory infiltrates consisting of interstitial and peribronchial lymphocytes and interalveolar macrophages were reported (13,66,91). Another autopsy study showed that severely damaged lungs from patients who died early had low interferon-stimulated genes (ISGs), low viral loads and abundant infiltrating activated CD8 + T cells and macrophages (71).…”
Section: Immune Cells In Covid-19 Lungmentioning
confidence: 99%